2019
DOI: 10.5039/agraria.v14i2a5630
|View full text |Cite
|
Sign up to set email alerts
|

Habilidade competitiva de cevada em convivência com densidades de azevém

Abstract: AGRONOMIA (AGRONOMY)RESUMO: A cultura da cevada vem ganhando espaço na região sul do Brasil, sendo uma importante opção para rotação de culturas no período de inverno. Um dos principais limitantes para o aumento da produtividade da cultura é a competição com plantas daninhas, principalmente o azevém. Sendo assim, objetivou-se com esse trabalho avaliar a habilidade competitiva da cevada (Hordeum vulgare) com o azevém (Lolium multiflorum) e mensurar em qual densidade de azevém há comprometimento do desenvolvimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(17 reference statements)
2
4
0
2
Order By: Relevance
“…In this same comparison, it was observed that the lowest competitiveness was verified for the cultivars BRS Korbel and BRS Cauê, which had the greatest losses in grain productivity, in relation to the others. Some studies have reported differentiation between the competition of different barley cultivars in the presence of ryegrass and/or turnip (Paynter and Hills 2009;Tironi et al 2014;Pies et al 2019), which is similar to the present study. The differences between barley cultivars in competition with turnip are due to distinct genetic characteristics, that is, differences in height, maturation cycle, leaf area index, root system, i and a = losses in productivity (%) per unit of ryegrass when the value of the variable approaches zero or tends to infinity, obtained by the rectangular hyperbola model Y = (i.X)/(1+(i/a).X (Cousens 1985), respectively.…”
Section: Economic Threshold Level Experimentssupporting
confidence: 91%
See 3 more Smart Citations
“…In this same comparison, it was observed that the lowest competitiveness was verified for the cultivars BRS Korbel and BRS Cauê, which had the greatest losses in grain productivity, in relation to the others. Some studies have reported differentiation between the competition of different barley cultivars in the presence of ryegrass and/or turnip (Paynter and Hills 2009;Tironi et al 2014;Pies et al 2019), which is similar to the present study. The differences between barley cultivars in competition with turnip are due to distinct genetic characteristics, that is, differences in height, maturation cycle, leaf area index, root system, i and a = losses in productivity (%) per unit of ryegrass when the value of the variable approaches zero or tends to infinity, obtained by the rectangular hyperbola model Y = (i.X)/(1+(i/a).X (Cousens 1985), respectively.…”
Section: Economic Threshold Level Experimentssupporting
confidence: 91%
“…Possibly the difference between the cultivars is partially due to different genetic characteristics, as already explained, such as height, cycle, leaf area index, root system, plant architecture, tillering, among others. This conclusion was also found in other studies in which the authors evaluated effects of crop cultivars in the presence of different weeds (Paynter and Hills 2009;Bajwa et al 2017;Galon et al 2019;Pies et al 2019;Tavares et al 2019). It should also be noted that the differentiation existing between barley cultivars may be related to more efficient use of environmental resources, or the occurrence of high stan dard error in the estimation of parameter i, attributed to the variability associated with field experimentation and/or the crop phenotypic plasticity (Agostinetto et al 2010;Galon et al 2019).…”
Section: Economic Threshold Level Experimentssupporting
confidence: 75%
See 2 more Smart Citations
“…The Brazilian average productivity of barley grains is 3.81 t•ha -1 , which is far below those obtained in experimental areas or in crops that adopt high technologies (CONAB 2022). Among the probable causes for this low productivity, we can highlight the interference caused by weeds, which compete with the crop for environmental resources, such as water, light, and nutrients (Pies et al 2019, Galon et al 2022. Weed infestation can also cause severe allelopathic effects or host pests and diseases (Tironi et al 2014, Pies et al 2019, Nichelati et al 2020, which can result in a decrease in barley grain yield of up to 78% (Mahajan et al 2020).…”
Section: Introductionmentioning
confidence: 99%